Orientasi Umum Ulumul Qur’an (Kajian Tentang Latar Belakang dan Perkembangannya dalam Dunia Islam) - Abdul Yazid Lingga (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the history and development of the ulumul quran, the research method used is qualitative with a literature study approach, while the results of the study explain that. Ulumul Quran itself is interpreted as discussions related to the Koran. Some of the main points of discussion of the science of the Qur'an can be viewed in terms of the revelation of verses, sequences of verses, collection of verses, writing of verses, reading of verses, interpretation of verses, i'jaz, nasikh and mansukh, or refutation of things that cause doubt. to the Qur'an. By understanding the Ulumul Quran we can recognize, understand and study about the ins and outs and matters related to Ulumul Quran. Where the process of providing information about what needs to be known from the Ulumul Quran, the information conveyed is in the form of asbabun nuzul, content, wisdom etc., from Ulumul Quran. Keywords: Ulumul Quran, Wahyu, Asbabun Nuzul, Tafsir